Effect of fuel temperature on the methanol spray and nozzle internal flow. (5th March 2017) - Chen, Zhifang; Yao, Anren; Yao, Chunde; Yin, Zenghui; Xu, Han; Geng, Peilin; Dou, Zhancheng; Hu, Jiangtao; Wu, Taoyang; Ma, Ming
Highlights: Cavitation region increases with the increasing of methanol temperature. The nozzle exit velocity increases with the increasing of methanol temperature. The discharge coefficient decreases with the increasing of methanol temperature. Droplet SMD reduces when methanol temperature increases measured by PDPA system. Droplet velocity has the maximum value when methanol temperature is 60 °C. Abstract: The increasing of fuel temperature can reduce the droplet size and have an advantage of improving spray atomization, while investigations of the effect of temperature on the methanol injector internal flow and external spray is rare. Firstly, a detailed three dimensional numerical simulations of nozzle internal flow have been conducted to probe into the cavitation in methanol injector nozzles, and then an experimental study has been carried out to investigate the droplet size and velocity of methanol spray at various temperatures using the Phase Doppler Particle Analyzer (PDPA) detecting system. And results show that the region of cavitations in nozzle orifice enlarges as methanol temperature and injection pressure increases, and the temperature for 'super-cavitation' occurring decreases gradually with the increasing of injection pressure. Moreover, the nozzle exit velocity, discharge coefficient and cavitations number were also analyzed. However, the discharge coefficient reduces nearly equal under various pressure when the methanol temperature is higher than 60 °C. In addition, the Sauter Mean Diameter (SMD) and velocity of methanol droplet were also analyzed, and found that the droplet velocity reaches the maximum value when the methanol temperature is 60 °C.